Melatonin Promotes in vitro Development of Vitrified-Warmed Mouse GV Oocytes, Potentially by Modulating Phosphorylation of Drp1 - Qin, Jianpeng; Guo, Shichao; Yang, Jinyu; Qazi, Izhar Hyder; Pan, Bo; Lv, Tianyi; Zang, Shengqin; Fang, Yi; Zhou, Guangbin (Frontiers in Veterinary Science, 2021)
Previous studies have shown that melatonin can mitigate cryopreservation-induced mitochondrial dysfunction in oocytes; however, the underlying molecular mechanism remains unclear. The objective of the present study was to investigate whether melatonin can improve the mitochondrial function during in vitro maturation of vitrified-warmed mouse germinal vesicle (GV) oocytes by modulating phosphorylation of dynamin related protein 1 (Drp1). Vitrification/warming procedures resulted in the following: 1) After cryopreservation of mouse GV oocytes, the phosphorylation level of Drp1 at Ser616 (p-Drp1 Ser616) in metaphase II (MII) oocytes was increased (P<0.05). Furthermore, the rates of in vitro maturation, cleavage and blastocyst formation after parthenogenetic activation were decreased (P<0.05). 2) In MII oocytes, the expression levels of translocase of the mitochondrial outer membrane 20 (TOMM20), mitochondrial membrane potential (MMP), adenosine triphosphate (ATP) content, and mRNA levels of mitochondrial biogenesis-related genes (Sirt1, Pgc-1α, Tfam) were all decreased (P<0.05). And 3) Reactive oxygen species (ROS) level, early apoptosis level, Cytochrome C release and mRNA levels of pro-apoptotic related genes (Bax, Caspase9, Caspase3) in MII oocytes were all increased (P<0.05). The results of this study further revealed that negative impacts of GV oocyte cryopreservation were mitigated by supplementation of warming and in vitro maturation media with 10-7mol /L melatonin or 2x10-5mol/L Mdivi-1 (Drp1 inhibitor). Therefore, we concluded that 10-7mol/L melatonin improved mitochondrial function, reduced oxidative stress and inhibited apoptosis by regulating phosphorylation of Drp1, thereby enhancing in vitro development of vitrified-warmed mouse GV oocytes.